Acceptability of emergency contraception in Brazil, Chile, and Mexico: 1 - Perceptions of emergency oral contraceptives - Díaz Soledad; Hardy Ellen; Alvarado Gloria; Ezcurra Enrique (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
This article presents the results of a study on the acceptability of emergency contraception (EC) in Brazil, Chile, and Mexico. Opinions of potential users and possible providers were obtained through discussion groups and those of authorities and policy-makers through semi-structured interviews. Most participants had a positive opinion of EC, based on the view that it can help reduce unplanned pregnancy, adolescent pregnancy, and unsafe abortion. Several interviewees felt that all women should be informed about EC, while others viewed it as a method for special situations such as rape and unprotected first sexual intercourse. Concern was expressed that its introduction might be associated with a decrease in condom use, increase in sexually transmitted diseases, and irresponsible or promiscuous sexual behavior among adolescents. The need for EC was clearly perceived by most participants, leading to the conclusion that health authorities have the responsibility of implementing programs for its introduction. Training of health care personnel should include the discussion of reproductive health problems that could be prevented by EC.